Ispolzovanie monitora serdechnogo ritma dlya kontrolya za effektivnostyu podgotovki bortsov - Pankov, V. A. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
The problem of regulation of training loads and regenerative processes at various stages of training has the important value for training of athletes in various kinds of sports wrestling and single combats. This article is devoted to the research of one of the aspects of this actual problem. The special value for regulation of training loads has the use of the cardiac rate data when single combats occupations. The author carried out the experimental researches to study the features of application of the cardiac rate monitor during training of wrestlers in various climatic conditions. During supervision the cardiac rate monitor Polar S-410 was applied. The application of the cardiac rate monitor in wrestlers' training has helped to solve the important pedagogical problems promoting the increase of efficiency of training process. The received data about the energy wasting by an athlete during training were used for an estimation of wrestlers' training loads, drawing up of a diet in usual conditions and at regulation and correction of the body weight.